SNR improvement and range side lobe suppression in Golay-encoded Doppler detection for ultrasound high-frequency swept-scan imaging system. (March 2018) - Yu, Jyun-Gong; Liu, Pin-Hsian; Shen, Che-Chou
Highlights: Conventional Golay decoding produces erroneous flow information due to range side lobe artifacts. The PRF /4 decoding can suppress the artifacts by slow-time processing in swept-scan color-flow imaging. Golay excitation is implemented in a 40-MHz pre-clinical imaging system with the PRF /4 decoding for in-vivo evaluation. Doppler SNR and penetration improves without artifacts when the axial motion velocity remains within ± PRF /4 limit. Abstract: Background: Golay excitation can be utilized to improve the signal-to-noise ratio (SNR). However, its application in ultrasound Doppler detection is limited due to potential motion artifacts in conventional decoding process. In this study, the improved Golay decoding has been implemented in a commercial 40-MHz pre-clinical system and experimentally verified for its efficacy in color-flow imaging. Methods: Based on the Doppler spectral difference of half pulse-repetition-frequency ( PRF ) between the main lobe and range side lobe components of Golay excitation, the slow-time decoding with a low-pass filter with cut-off frequency of PRF /4 can separate the desired main lobe from the side lobe interference. The Prospect ® system has been customized to generate the Golay transmit sequence in swept-scan mode and to perform the PRF /4 decoding for in-vivo evaluation of mouse blood flow. Results: Results indicate that the PRF /4 decoding can effectively eliminate the range side lobe artifacts in phantom experiments for flow velocity not exceeding the limit of ± PRF /4 in Doppler frequency. For in-vivo imaging, the SNR improves by about 7 dB and the Doppler penetration increases from 13.5 mm to 14.2 mm in mouse kidney when the transmit is switched from un-coded to Golay excitation. In mouse abdominal aorta, the Golay transmit also increases the Doppler sensitivity. Conclusion: Golay-encoded color-flow imaging has been established using the pre-clinical system to achieve SNR improvement in Doppler detection without suffering from the range side lobe artifacts. To guarantee the performance of PRF /4 decoding, the side lobe aliasing should be avoided by carefully selecting the PRF to the match the flow velocity.